Demographic and behavioral correlates of HIV/STI among Vietnamese female sex workers in southwest China. Issue 11 (1st November 2016) - Yu, Yeon Jung; Li, Xiaoming; Tam, Cheuk Chi; Zhou, Yuejiao; Chen, Yi; Shen, Zhiyong
ABSTRACT: Previous literature has suggested high rates of HIV/STIs among Chinese FSWs. However, limited data were available regarding HIV-related risks among Vietnamese FSWs – a rapidly increasing, vulnerable population in southwest China. The current study examined the demographic and behavioral factors associated with the infection rates of HIV, syphilis, and Hepatitis C (HCV) among Vietnamese FSWs in Guangxi, China. We conducted a secondary data analysis of a cumulative sample of 1026 Vietnamese FSWs (aged 14–66) recruited over five years (2010–2014) from 35 National Sentinel Surveillance sites in Guangxi. Analyses included Fisher's exact chi-square test, t -test, and binary logistic regression. The overall prevalence of HIV, syphilis, and HCV infections among the cross-border women were 3.2%, 6.9%, and 2.6%, respectively. Multivariate analysis showed that greater lengths of sex work and low paying work venues were significant risk factors for HIV infection; for syphilis infection, older age, drug use experience, and forgoing condom use were significant risk factors; for HCV infection, drug use experience was the only significant risk factor. Our findings suggest that elevated HIV-related risks among the Vietnamese FSWs are closely related to their financial disadvantages and that drug use is a prominent risk factor for cross-border women in the sex trade. Furthermore, culturally tailored and linguistically accessible HIV prevention and intervention initiatives that target cross-border FSWs, with a close international collaboration between China and Vietnam, are urgently needed.